Clinical Penetrance of Hereditary Hemochromatosis-Related End-Organ Damage of C282Y Homozygosity, A Newfoundland Experience - Lim, Dennis R. (Clin Transl Gastroenterol, 2020)
Hereditary hemochromatosis is an autosomal recessive disorder of iron absorption, leading to organ dysfunction. C282Y gene homozygosity is implicated in 80%–95% of cases of hereditary hemochromatosis. The clinical penetrance of this genotype remains unclear. The purpose of the study was to better describe the clinical penetrance and disease progression of C282Y homozygotes. METHODS: This is a retrospective study of all individuals in Newfoundland and Labrador, Canada, homozygous for the C282Y mutation from 1999 to 2009. Using electronic health records, laboratory values, phlebotomy status, radiologic reports, and clinic records were recorded up to November 2017. Iron overload status was classified via the HealthIron study. SPSS Version 19.0 (IBM Corporation) was used for descriptive statistics. Predictors of disease penetrance were assessed with logistic regression; a Student t test was used for continuous variables, and χ(2) tests were used for categorical variables. RESULTS: Between 1999 and 2009, 360 individuals tested positive for C282Y/C282Y. The mean age of diagnosis was 49.1 years. Three hundred six individuals had adequate follow-up for analysis (mean 11.6 years). End-organ damage was observed in 18.3%, with 5.8% developing liver disease. End-organ damage was more frequently observed in men 24.3% vs 10.5% (P < 0.05). Clinical penetrance in postmenopausal women approached that of men 18.3%. DISCUSSION: This is the largest reported cohort of C282Y homozygotes, followed for an extended duration of time in North America. The findings reflect outcomes in routine clinical practice and suggest that C282Y homozygosity uncommonly causes end-organ damage and liver disease.